Horehound (Marrubium vulgare L.) as natural dietary feed additive in rabbit: effects on productive traits, antioxidant status, caecal environment, and gut morphology - Losacco, Caterina; Pugliese, Gianluca; Passantino, Letizia; Giannico, Francesco; Ceci, Edmondo; Roselli, Vincenzo; Gambacorta, Lucia; Schiavitto, Michele; Laudadio, Vito; Piemontese, Luca; Tufarelli, Vincenzo (Frontiers in Animal Science, 2025)
Marrubium vulgare L., commonly known as horehound in Europe, belongs to the Lamiaceae family, one of the most prominent medicinal plant families in the Mediterranean region. Traditionally used in herbal medicine, horehound contains a broad spectrum of bioactive compounds, supporting its potential use as a natural feed additive in animal nutrition. This study evaluated the effects of dietary horehound powder (HP) on growth performance, serum antioxidant status, digestive enzyme activity, intestinal microbial populations, and gut and liver histomorphology in growing rabbits. Eighty weaned male Bianca Italiana rabbits (42 days old) were randomly assigned to two dietary groups for a 6-week feeding trial: a control group fed a basal diet and a treatment group receiving the same diet supplemented with 0.15% HP (1.5 g/kg). At slaughter (84 days of age), samples of meat, blood, liver, and intestinal tissue were collected for analysis. Dietary HP significantly improved final body weight, feed conversion ratio, and carcass yield (P < 0.01), with no notable differences in proximate meat composition. However, meat from HP-fed rabbits showed increased total polyunsaturated fatty acids (PUFAs) (P < 0.05) and n-6 fatty acids (P < 0.01). Serum lipid profiles remained unaffected, while serum antioxidant parameters—total antioxidant capacity (TAC), malondialdehyde (MDA), and superoxide dismutase (SOD)—were significantly enhanced in the HP group. Additionally, HP supplementation increased the activity of duodenal α-amylase, maltase, lipase, and trypsin (P < 0.05). Although caecal morphology did not differ significantly between groups, rabbits receiving HP exhibited higher Lactobacillus spp. counts and reduced Escherichia coli populations. Duodenal histomorphometry showed significant improvements in villus height, crypt depth, and the villus height to crypt depth ratio (P < 0.01). No histological alterations were observed in the liver of rabbits. In conclusion, dietary inclusion of horehound powder positively influenced growth performance, oxidative status, digestive enzyme activity, and intestinal health in rabbits, supporting its use as a functional feed additive in sustainable rabbit production.